Influence of carbon on structure stability, mechanical and tribological properties of β-Si3(Cx, N1−x)4 silicon carbonitride. (9th May 2018) - Zhong, Jing; Hua, Guomin; Chen, Linbo; Li, Changsheng; Yang, Jianhong; Cheng, Xiaonong
Abstract: In this study, β -Si3 (Cx, N1−x )4 Silicon Carbonitride was prepared by Self-Propagation High-Temperature Synthesis (SHS). And the influence of carbon on structure stability, mechanical and tribological properties of β -Si3 (Cx, N1−x )4 were investigated. The results showed that the solubility of carbon in β -Si3 (Cx, N1−x )4 was about 10 wt%, beyond which cubic-SiC segregated out of β -Si3 (Cx, N1−x )4 to form β -Si3 N4 /cubic-SiC composite. Regarding influences of carbon concentration on mechanical properties, the hardness of β -Si3 (Cx, N1−x )4 decreased from 1400 Hv to 1200 Hv with the increase of carbon concentration. Whereas, the fracture toughness of β -Si3 (Cx, N1−x )4 increased from 6.5 MPa · m 0.5 to 7.6 MPa · m 0.5 with the increase of carbon concentration. The tribological property studies revealed the anti-wear performance of β -Si3 (Cx, N1−x )4 was enhanced by the increase of carbon concentration. The dominated wear mechanism could be attributed to the abrasive wear by fracture.